Reação de híbridos de citros à inoculação com Alternaria alternata e estudos genéticos associados - Michielin, Thais Helena Villa (Universidade Federal de São Carlos, 2016)
Alternaria Brown Spot (ABS), caused by Alernaria alternata a fungus which produces a host specific toxin (HST), is a disease of huge importance in mandarin orchards in many producing regions in the world. The selection of varieties resistant to disease is of great economic importance. In this study different hybrids of citrus were evaluated. These hybrids were obtained by directed crosses and preselected by agronomic characteristics that make them potential new varieties of oranges and mandarins, for industry or fresh fruit. The evaluation of these new genotypes is an essential step for the release of new varieties. Seventy-nine hybrids and their parents were subjected to inoculation with an isolated from A. alternaria in detached leaves and plant assays. The severity of disease was measured by the scale described in the literature. The evaluation of Mendelian segregation in hybrids of Murcott tangor and Pera sweet orange, evaluated in greater numbers, allows inference about the genetics of resistance heritability of ABS and to map the genomic region associated with the fungus using an integrated genetic map previously obtained. Different responses were observed after the fungus inoculation. Five hybrids of Willowleaf mandarin like, six hybrids of mandarin like, three hybrids of Murcott like and 21 hybrids of orange like, resistant to ABS, or with few symptoms of the disease were selected. High values of heritability and genetic variability measured indicate that the selection of resistant plants in the progeny can be successful. A resistance gene and molecular markers associated with it were located in the same linkage group 3 of integrated map of Murcott and Pera. The selected genotypes constitute potential material for commercial planting and for the control of disease in the field.
Citrus hybrids reaction to inoculation with a. alternata and genetic studies associated
Keywords: Tangerinas; Fungo; Melhoramento; Citricultura; Mma; CIENCIAS AGRARIAS